STUDENTS’ GRAMMAR IN WRITING SHORT DIARY AT SMA NEGERI 3 BAUBAU - Mido, La (English Education Journal, 2023)
The problrm statement of this research was “”was the use of writing short diary effective on English Grammar at the second year of SMA Negeri 3 Baubau. The objective of the research was to know the significant effect of writing “short diary” on English grammar at the second year of SMA Negeri 3 Baubau.The method used in this research was quasy experimental design with non equivalent control group design.. The sample of this research was 46 students namely IPA II as control class and IPA III as experimental class. Cluster random sampling used to take the students’ of English grammar achievement. The instrument of this research was objective test. The data collected through the pretest and posttest. The research was analyzed through quantitative statistics describe.Based on the result of the research that in experimental class students’ score on posttest showed that the mean score 73.13 was higher than in pretest 48.95. In control class student’s score on pretest showed that the mean score was 50.69, and in posttest showed that the mean score 61.39.. Therefore it can be concluded that writing short diary can increase the students’ ability in English grammar especially past tense at the second year of SMA Negeri 3 Baubau.